Activity rhythm and action range of workers of the invasive hornet predator of honeybees Vespa velutina, measured by radio frequency identification tags. Issue 15 (8th July 2018) - Poidatz, Juliette; Monceau, Karine; Bonnard, Olivier; Thiéry, Denis
Abstract: In social insects, the activity rhythm of foragers and their action range determinate the activity of the colony. In vespids, which are mostly predators, the foraging range of workers determines their maximum predation pressure round the nest. One of these species, Vespa velutina, a recently invasive species introduced into Europe, exerts a strong predation on honeybees at the hive. Therefore, the definition of its activity rhythm and spatial range of predation is of primary importance. Using radio frequency identification tags (RFID), two experiments were carried out to (a) determine their return ability (called homing) in releasing 318 individuals at different distance from their colony and (b) monitor their foraging activity rhythm and the duration of their flights based on 71 individuals followed 24 hr/24 during 2 months. The homing ability of V. velutina was evaluated to be up to 5, 000 m and was not affected by the cardinal orientation of release point. The lag time to return to the nest increased with the distance of release. Most of the flight activity took place between 07:00 a.m. and 08:00 p.m., hornets doing principally short flights of less than an hour. Foraging range was thus estimated ca. 1, 000 m around the nest. This study of V. velutina assisted by RFID tags provides for the first time a baseline for its potential foraging distance that increase our knowledge of this species to (a) refine more accurately models for risk assessment and (b) define security perimeter for early detection of predation on invasion front. Abstract : RFID for monitoring the invasive honeybee predator Vespa velutina : deciphering the activity rhythm and the action range.